2000
DOI: 10.1063/1.1328067
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Franck–Condon absorption and emission spectra of conjugated oligomers from quantum chemistry

Abstract: A harmonic Condon approach is used to calculate excitation and emission band shapes for the lowest dipole-allowed electronic transitions in conjugated oligomers: polyenes, oligorylenes, and para-phenylenevinylenes. Ground- and excited-state adiabatic energies, equilibrium structures, and vibrational modes are obtained within standard all-valence-electron molecular Hamiltonian incorporating extended configuration interaction. The interstate distortion is cast in normal coordinates and used to calculate transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
131
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(160 citation statements)
references
References 44 publications
20
131
1
1
Order By: Relevance
“…Common to both, however, are contributions from modes around 1600 cm −1 and 1800 cm −1 . These correspond to the C=C bond stretching modes and are consistent with the the vibronic fine-structure peaks observed in most conjugated polymer systems 18,19 . Fig.…”
Section: Obtaining Model Parameters From Quantum Chemistysupporting
confidence: 84%
“…Common to both, however, are contributions from modes around 1600 cm −1 and 1800 cm −1 . These correspond to the C=C bond stretching modes and are consistent with the the vibronic fine-structure peaks observed in most conjugated polymer systems 18,19 . Fig.…”
Section: Obtaining Model Parameters From Quantum Chemistysupporting
confidence: 84%
“…This can be readily done within the Condon approximation for displaced multidimensional harmonic oscillators [20,33]. The vibrational overlap integrals | 0|ν n | 2 = e −Sn S ν n ν!…”
Section: Computational Methodologymentioning
confidence: 99%
“…These quantities, in turn, depend on the dimensionless displacements ∆ n of each normal mode with HuangRhys factors, S n = ∆ 2 n /2. The fluorescence band shape as a function of the frequency ω is determined by the imaginary part of the polarizability [20,33] …”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically Karabunarliev et al studied the oligorylenes by using different semiempirical and concluded that for quaterrylene, the optically opaque state becomes the lowest excited state adiabatically, not vertically, while for shorter rylenes, the lowest excited states are dipole-allowed both adiabatically and vertically. [28][29][30] Therefore, there certainly occurs a 1Bu/2A g crossover when elongating oligorylenes length, and terrylene and quaterrylene may be both close to the crossover point.…”
Section: Introductionmentioning
confidence: 99%